Senior Alert: A Quality Registry to Support a Standardized, Structured, and Systematic Preventive Care Process for Older Adults. Issue 2 (April 2015) - Edvinsson, Joakim; Rahm, Magnus; Trinks, Anna; Höglund, Pär J.
Abstract : The average life expectancy and the proportion of the elderly in the Western countries are increasing. The care processes used for the elderly are known to differ between the care providers in Sweden. Accordingly, the need to develop a system to support the processes in order to attain a standardized, structured, and systematic approach to improve preventive care processes for the elderly has been called for. The County Council of Jönköping developed a national Web-based quality registry, Senior Alert, with a focus on the following areas: falls, pressure ulcers, malnutrition, and oral health. The patients are evaluated using validated risk assessment instruments, and the care is planned, executed, evaluated. The registry supports the users to work with preventive care systematically and in a standardized way and provides feedback to the care providers on their preventive care processes. The registry helps the caregivers fulfill the preventive care according to the best available clinical knowledge and practice. The registry also provides the government and health care politicians with data for setting aims for elderly care. The registry is used in 90% of the municipalities and county councils throughout the country. The total number of risk assessments completed from 2009 to 2014 exceeded 1 000 000.